PENGARUH GAYA HIDUP DAN KELOMPOK ACUAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN WARKOP ONTAJAWA KABUPATEN GRESIK) - Maulana, Reza Rifanda Dwi Candra; Maulana, Maulana (LP2M Universitas Bina Bangsa, 2025)
This study aims to evaluate the impact of lifestyle (x1) and reference group (x2) variables on purchase decisions (y), both individually and collectively. Utilizing a quantitative approach, the research involves 100 visitors to Warkop Ontajawa in Gresik, and analysis is performed using SEM-PLS with SmartPLS 3.0 software. The results indicate that both lifestyle (x1) and reference group (x2) variables have a significant impact on purchase decisions, with p-values < 0.05 for both variables. The F-test shows an F-value of 78.132, exceeding the F-table value of 3.090, indicating a significant simultaneous effect of both independent variables on the dependent variable, purchase decisions (y). In conclusion, both lifestyle and reference group significantly influence the purchase decisions of Warkop Ontajawa visitors